Keefektifan Strategi Rekayasa Teks dalam Pembelajaran Menulis Laporan Ilmiah Siswa Kelas XII SMK Negeri 7 Bone - Marwah, Marwah; Nensilianti, Nensilianti; Dalle, Ambo (ppjbsip, 2025)
This study aims to describe the effectiveness of text engineering strategies, modeling strategies, and the differences between text engineering strategies and modeling strategies in learning to write scientific reports for grade XII students of SMKN 7 Bone. This study uses a quantitative approach. The data collection technique is in the form of a test to write scientific reports. The results of the study show that text engineering strategies are effectively used in learning to write students' scientific reports. The results of the t-test showed that the score was 18,058 > a value of 2,093 with a value of sig. (2-tailed) of 0.000 < 0.05 so that H1 is accepted. The mean value of students' text engineering strategies before treatment was 48.75 with the low category, after treatment increased to 82.05 in the high category. Effective modeling strategies are used in learning to write scientific reports. The results of the t-test showed that the score was 23,614 > a score of 2,093 with a sig value. (2-tailed) of 0.000 < 0.05 so that H1 is accepted. The mean value of students' modeling strategies before treatment was 44.85 with the low category, after treatment increased to 84.05 with the high category. There was no significant difference between the two classes in learning to write scientific reports after being treated. Abstrak Penelitian ini bertujuan mendeskripsikan keefektifan strategi rekayasa teks, strategi modeling, dan perbedaan antara strategi rekayasa teks dan strategi modeling dalam pembelajaran menulis laporan ilmiah siswa kelas XII SMKN 7 Bone. Penelitian ini menggunakan pendekatan kuantitatif. Teknik pengumpulan datanya berupa tes menulis laporan ilmiah. Hasil penelitian menunjukkan strategi rekayasa teks efektif digunakan dalam pembelajaran menulis laporan ilmiah siswa. Hasil uji t-test menunjukkan bahwa nilai sebesar 18.058 > nilai sebesar 2.093 dengan nilai sig. (2-tailed) sebesar 0,000 < 0,05 sehingga H1 diterima. Nilai mean strategi rekayasa teks siswa sebelum perlakuan adalah 48,75 dengan kategori rendah, setelah perlakuan meningkat menjadi 82,05 kategori tinggi. Strategi modeling efektif digunakan dalam pembelajaran menulis laporan ilmiah. Hasil uji t-test menunjukkan bahwa nilai sebesar 23.614 > nilai sebesar 2.093 dengan nilai sig. (2-tailed) sebesar 0,000 < 0,05 sehingga H1 diterima. Nilai mean strategi modeling siswa sebelum perlakuan adalah 44,85 dengan kategori rendah, setelah perlakuan meningkat menjadi 84,05 dengan kategori tinggi. Tidak terdapat perbedaan yang signifikan antara kedua kelas dalam pembelajaran menulis laporan ilmiah setelah diberi perlakuan.